2013
DOI: 10.1523/jneurosci.2121-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Glial Scar Borders Are Formed by Newly Proliferated, Elongated Astrocytes That Interact to Corral Inflammatory and Fibrotic Cells via STAT3-Dependent Mechanisms after Spinal Cord Injury

Abstract: Astroglial scars surround damaged tissue after trauma, stroke, infection, or autoimmune inflammation in the CNS. They are essential for wound repair, but also interfere with axonal regrowth. A better understanding of the cellular mechanisms, regulation, and functions of astroglial scar formation is fundamental to developing safe interventions for many CNS disorders. We used wild-type and transgenic mice to quantify and dissect these parameters. Adjacent to crush spinal cord injury (SCI), reactive astrocytes ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

39
763
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 663 publications
(864 citation statements)
references
References 63 publications
39
763
2
5
Order By: Relevance
“…4 A and B), reminiscent of gliaguided migration of newborn neurons in the developing cortex (19,20). Astrocytes at the lesion appeared to lose their stellate morphology and to adopt overlapping, elongated morphologies (21) (Fig. 4C).…”
Section: Resultsmentioning
confidence: 93%
“…4 A and B), reminiscent of gliaguided migration of newborn neurons in the developing cortex (19,20). Astrocytes at the lesion appeared to lose their stellate morphology and to adopt overlapping, elongated morphologies (21) (Fig. 4C).…”
Section: Resultsmentioning
confidence: 93%
“…Reactive astrocytes are not one homogenous type of cell but instead display distinct morphological and functional properties in zones that extend away from the infarct or central nervous system injury. This has been best detailed in the injured spinal cord and in normal brain, where distinct morphologies of reactive astrocytes indicate likely different zones of tissue repair and recovery [70], or of distinct circuit function [71]. In stroke, distinct types of reactive astrocytes are also present.…”
Section: Radial Stroke: Tissue Reorganizationmentioning
confidence: 99%
“…Dynamic changes to astrocyte-neuron interaction mediated by changes to distal astrocytic processes are known to influence neuron-astrocyte plasticity (15). Although astrocytes are generally stationary cells that provide a supportive network for neuronal cells and synapses, migratory and proliferating astrocytes have been observed in glial scarring, an environment with diminished neuronal function (43,44). In this study, an altered cellular environment in the form of nanotopography was shown to affect astrocyte biophysical attributes (shape and roughness) so as to alter their interaction with neurons.…”
Section: Regions Of Amyloid Plaque Buildup In Alzheimer's Present Incmentioning
confidence: 99%